Hubungan Konsumsi Sayur dan Buah dengan Kegemukan Remaja di Kota Padang - Elsyie Yuniarti (Poltekkes Kemenkes Padang, 2023)
Less consumption of vegetables and fruit in adolescents causes obesity. Vegetables and fruit are sources of fiber, vitamins and minerals. The aim of the study was to determine the relationship between vegetable and fruit consumption and obesity in adolescents in Padang City. This research is a quantitative research with an analytic type using an observational cross sectional study design. Data collection in June-August 2022 at four high schools in the city of Padang with a total sample of 240 respondents. The sampling technique is multi-stage random sampling. Analysis using the chi square test. The results showed that there was no significant relationship between vegetable consumption habits and obesity in adolescents with a value of p=0.273, there was a relationship between the portion of vegetable consumption and obesity in adolescents with a value of p=0.000, there was no relationship between fruit consumption habits and obesity in adolescents with p = 0.121, there is a relationship between fruit consumption and obesity in adolescents with p = 0.049. Conclusion: The prevalence of obesity in adolescents in Padang City is 19.6%, more than 50% of adolescents have a habit and portion of consuming vegetables and fruit that is still lacking. It is recommended that adolescents have the habit of consuming vegetables and fruit as recommended, namely ≥3 servings/day (≥250 gr/day) of vegetables and ≥3 servings/day (≥150 gr/day) of fruit.